Analisis Faktor-faktor Produktivitas Padi di Jawa Barat Tahun 2018-2024 - Adiansyah; Jeane Talakua (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the influence of land area variables, climate, fertilizer subsidies, and domestic investment on West Java rice production in 2018-2024. The approach in this study uses a quantitative approach with data in the form of secondary data. The location determination was carried out by the purposive method in the period 2018-2024. The analysis techniques used were in the form of multiple linear regression analysis of panel data with classical assumption test, model specification test, t test, f test, and determination coefficient test. The results of the study show that land area has a significant positive effect on rice production. Meanwhile, climate and domestic investment have a significant negative effect on rice production. And fertilizer subsidies do not have a significant effect on West Java rice production. And the variable that has the most influence on rice production is Land Area.